Hypoxia-Responsive Oxygen Nanobubbles for Tissues-Targeted Delivery in Developing Tooth Germs - Kim, Eun-Jung; Lee, Ji-Eun; Yoon, Semi; Lee, Dong-Joon; Mai, Han Ngoc; Ida-Yonemochi, Hiroko; Choi, Jonghoon; Jung, Han-Sung (Frontiers in Cell and Developmental Biology, 2021)
Hypoxia is a state of inadequate supply of oxygen. Increasing evidence indicates that a hypoxic environment is strongly associated with abnormal organ development. Oxygen nanobubbles (ONBs) are newly developed nano materials that can deliver oxygen to developing tissues, including hypoxic cells. However, the mechanisms through which nanobubbles recover hypoxic tissues, such as developing tooth germs remain to be identified. In this study, tooth germs were cultured in various conditions: CO2 chamber, hypoxic chamber, and with 20% ONBs for 3 h. The target stages were at the cap stage (all soft tissue) and bell stage (hard tissue starts to form). Hypoxic tooth germs were recovered with 20% ONBs in the media, similar to the tooth germs incubated in a CO2 chamber (normoxic condition). The tooth germs under hypoxic conditions underwent apoptosis both at the cap and bell stages, and ONBs rescued the damaged tooth germs in both the cap and bell stages. Using kidney transplantation for hard tissue formation in vivo, amelogenesis and dentinogenesis imperfecta in hypoxic conditions at the bell stage were rescued with ONBs. Furthermore, glucose uptake by tooth germs was highly upregulated under hypoxic conditions, and was restored with ONBs to normoxia levels. Our findings indicate that the strategies to make use of ONBs for efficient oxygen targeted delivery can restore cellular processes, such as cell proliferation and apoptosis, glucose uptake, and hypomineralisation in hypoxic environments.